Giant Pyonephrosis in an Ectopic Kidney: A Case Report - Ahmed MM; Adem MB; Mideksa AG; Huluka TY (Research and Reports in Urology, 2023)
Mensur Mohammed Ahmed,* Mubarek Bargicho Adem,* Adugna Getachew Mideksa,* Tolesa Yadeta Huluka Department of Surgery Urology Division, Saint Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia*These authors contributed equally to this workCorrespondence: Mensur Mohammed Ahmed, Tel +251978191741, Email mensurm69@gmail.comAbstract: Pyonephrosis is characterized by infective hydronephrosis accompanied by suppurative destruction of the renal parenchyma, resulting in partial or complete impairment of renal function. Patients present with wide range of symptoms, they can be asymptomatic in 15% but most of them present with septic features like fever, chills, and flank pain. Urinary tract infections, functional and anatomic obstruction, and anatomic anomalies such as pelvic and horseshoe kidneys are common etiologic factors. We report a 30 years old female patient with giant pyonephrosis in an ectopic kidney. She presented with acute toxic symptoms after she has been experiencing progressive abdominal swelling and pain for a couple of years. Simple nephrectomy was done four weeks after she has been initially treated with percutaneous drainage of the pus and intravenous antibiotics.Keywords: giant pyonephrosis, ectopic kidney, percutaneous nephrostomy, simple nephrectomy